Administrative procedures in the field of local taxation - Yuriichuk, Illia (European Journal of Law and Public Administration, 2018)
In the article analyzes the features of administrative procedures in the local taxation system. It’s determined that at the present stage of development of our state, the unconditional fact is that the development of the institute of administrative procedural law in Ukraine is one of the main tasks of administrative reform, the purpose of which is to create a proper and highly developed system of public administration bodies that will ensure and guarantee the protection of rights, freedoms and the legitimate interests of each person. Increasing the efficiency of the work of the State fiscal service and its territorial bodies in the field of taxation directly depends on the effectiveness of administrative procedures, which, of course, is one of the basic components of administrative reform. The author pays his attention that the effective functioning of the Ukrainian tax system is impossible without proper administrative procedures and a reliable system of administering local taxes and fees. Established in 2011, the Tax Code of Ukraine introduced significant changes in the process of administering local taxes and fees, but today there are a number of problems, namely: the lack of quality regulatory administrative procedures, the lack of a unified approach to the definition of "administrative procedure" and the presence of gaps in the practical aspect of the functioning of the tax system. The conclusions is drawn about the definition of the concept of administrative procedures in the field of local taxation and the improvement of Ukrainian legislation in the area of local taxation in order to protect the rights and interests of taxpayers.
Keywords: administrative procedures; tax system; local taxes and fees; administering of local taxes and fees; rights and legitimate interests of taxpayers